2020
DOI: 10.1101/2020.10.13.20212092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Neanderthal OAS1 isoform Protects Against COVID-19 Susceptibility and Severity: Results from Mendelian Randomization and Case-Control Studies

Abstract: Proteins detectable in peripheral blood may influence COVID-19 susceptibility or severity. However, understanding which circulating proteins are etiologically involved is difficult because their levels may be influenced by COVID-19 itself and also subject to confounding factors. To identify circulating proteins influencing COVID-19 susceptibility and severity we undertook a large-scale two-sample Mendelian randomization (MR) study, since this study design can rapidly scan hundreds of circulating proteins and r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
1
12
0
2
Order By: Relevance
“…Our findings thus suggest that persisting archaic introgressed haplotypes provided a reservoir of functional variation to the ancestors of CDX and KHV that proved adaptive during a period of environmental change, for example in response to local pathogens (Rasmussen et al, 2015). Recent reports that Neanderthal-introgressed sequences mediate individual outcomes of SARS-CoV-2 infections to this day lend plausibility to this hypothesis Pääbo, 2020a, 2020b) (Zhou et al, 2020), as does polygenic evidence of adaptation in response to ancient viral epidemics, including in East Asia (Souilmi et al, 2021).…”
Section: Discussionsupporting
confidence: 51%
“…Our findings thus suggest that persisting archaic introgressed haplotypes provided a reservoir of functional variation to the ancestors of CDX and KHV that proved adaptive during a period of environmental change, for example in response to local pathogens (Rasmussen et al, 2015). Recent reports that Neanderthal-introgressed sequences mediate individual outcomes of SARS-CoV-2 infections to this day lend plausibility to this hypothesis Pääbo, 2020a, 2020b) (Zhou et al, 2020), as does polygenic evidence of adaptation in response to ancient viral epidemics, including in East Asia (Souilmi et al, 2021).…”
Section: Discussionsupporting
confidence: 51%
“…LPS levels were investigated in a prospective study on 19 patients with severe pulmonary forms of COVID-19; almost 90% of them had increased LPS levels—40% demonstrated high and 30% demonstrated very high endotoxin levels [ 9 ]. Application of mendelian randomization using 6,492 hospitalized cases and over 1 million controls demonstrated that serum LBP levels strongly correlate with the hospitalization rate of COVID-19 patients [ 10 ]. The plasma levels of LBP were also investigated in 39 hospitalized patients with severe COVID-19 with significant cardiac pathology; these levels were initially high and remained high during hospitalization [ 11 ].…”
mentioning
confidence: 99%
“…We identified a few other genes involved in viral response that were upregulated in patients with active COVID-19 infection. Increased OAS1 levels confer protection against severe COVID-19 [18] and this family of antiviral genes has been shown to be associated with the host response [19].…”
Section: Up-regulation Of Immune Related Genes and The Interferon-mediated Immune Responsementioning
confidence: 99%